SOCIAL ISSUES IN THE AZERBAIJAN OIL INDUSTRY AT THE END OF THE XIX CENTURY - Hajiyev, Ilgar (European Scientific Journal, ESJ, 2015)
This article is about social issues in the Azerbaijan oil industry at the end of the XIX century when Azerbaijan was colony of Tsarist Russian Empire. Workers’ wages and work hours, living and working condition, religious issues, education and health problems have been studied in this article.